Impact of China's trade imbalance on Malaysia and Indonesia's mining sector: Implications for sustainable economic growth - Ekowati, Pratiwi Dian (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: The People's Republic of China (PRC) has had a profound impact on international trade in Southeast Asia, particularly for Malaysia and Indonesia, through its trade imbalances and shifting economic policies. This study examines how Malaysia and Indonesia have adapted their trade strategies in the mining sector in response to these changes. Methods: Using a qualitative research approach, it analyzes data from trade reports, economic literature, and statistical databases to compare Malaysia’s dual-economy strategy with Indonesia’s focus on domestic resource processing. Findings: Malaysia has implemented a dual economic strategy, focusing on processing and exporting finished goods, while Indonesia has prioritized improving domestic processing capabilities, particularly for nickel, to reduce dependence on raw resource exports. China's Belt and Road initiative has influenced further bilateral collaboration, such as the establishment of industrial parks in both countries. While these strategies have driven growth, challenges remain in ensuring sustainable trade practices and optimizing economic outcomes. Conclusion: These findings highlight the need for mutually beneficial policies to enhance Malaysia and Indonesia's position in global trade dynamics. Novelty/Originality of this article: The novelty of this study lies in the comparative analysis of Malaysia and Indonesia's trade strategies in the mining sector in response to China's economic policy changes, including the impact of the Belt and Road Initiative.